Is there any association between foot posture and lower limb-related injuries in professional male basketball players? A cross-sectional study - Lopezosa-Reca, E.; Gijon-Nogueron, G.; Morales-Asencio, J. M.; Cervera-Marin, J. A.; Luque-Suarez, A. (Clinical Journal of Sport Medicine, 2020)
Several studies have shown that foot posture is related to the incidence of ankle sprains in athletes and in nonathletic populations, but this association has not previously been considered in basketball players. This study investigates the relationship between foot posture and lower limb injuries in elite basketball players. Design and Method: Two hundred twenty participants were recruited as a convenience sample. The players had a mean age of 22.51 ± 3.88 years and a body mass index of 23.98 ± 1.80. The players' medical records were accessed from the preceding 10 years, and injuries were recorded according to their location (knee, foot, and/or ankle). In addition, the Foot Posture Index (FPI) was scored for each player, and their playing positions were noted. Results: An average FPI score of 2.66 was obtained across all players, with guards presenting a significantly lower average FPI of -0.48 (P < 0.001) compared with the rest of playing positions, indicating a more supinated foot. However, center players presented an average FPI of 5.15 (P < 0.001), indicating a more pronated foot. The most common injuries observed were lateral ankle sprain (n = 214) and patellar tendinopathy (n = 126). Patellar tendinopathy was more common in supinated feet (30.08%) compared with 20.7% and 19.8% in pronated and neutral feet, respectively. Conclusions: The most common lower limb injuries observed in basketball players were lateral ankle sprain and patellar tendinopathy. Patellar tendinopathy was more commonly associated with the supinated feet. Guard players tended to have a more supinated foot, whereas centers presented a more pronated foot.